Long-term low-dose oxytetracycline potentially leads to neurobehavioural changes - Yushu Qiu; Kan Yu; Xiaogang Yu; Xiaoping Yi; Kang Cai; Huajun Li; Shanshan Xu; Weiye Wang; Lisu Huang (Ecotoxicology and Environmental Safety, 2021)
Trace levels of oxytetracycline (OTC)—a veterinary antibiotic and feed additive—are widespread in the environment. Studies revealed that OTC potentially impairs thyroid function, which may affect neurobehaviour; however, the impact of exposure to environmental concentrations of OTC on adult neurobehaviour is unknown. In this study, the effects of OTC on zebrafish after 30-day exposure were investigated. The total swimming distance was significantly increased under vibration and light/dark stimulation, while time spent in the white area was prolonged during the black/white preference test, indicating that the zebrafish became bolder and more impulsive under low OTC exposure. Additionally, monoamine neurotransmitter (5-hydroxytryptamine, dopamine, norepinephrine) levels were decreased and gene expression of monoamine oxidase (mao) involved in neurotransmitter metabolism was upregulated at the transcription level after OTC exposure. Because triiodothyronine (T3) levels were enhanced following exposure to OTC, we speculated that T3 may mediate OTC damage to the nervous system. Our simulated molecular docking analysis showed that OTC combined with the sodium iodide cotransporter protein may result in excessive T3 synthesis. We further exposed zebrafish to T3, and they exhibited similar behaviour to the OTC exposure group. In conclusion, environmental OTC may activate monoamine oxidase and enhance the metabolism of monoaminergic neurotransmitters via T3, thereby inducing abnormal neurobehaviour.